The American Isherwood - Freeman, Chris, 1965-; Berg, James J. (Book collections on Project MUSE., 2015)
"Novelist, memoirist, diarist, and gay pioneer Christopher Isherwood left a wealth of writings. Known for his crisp style and his camera-like precision with detail, Isherwood gained fame for his Berlin Stories, which served as source material for the hit stage musical and Academy Award-winning film Cabaret. More recently, his experiences and career in the United States have received increased attention. His novel A Single Man was adapted into an Oscar-nominated film; his long relationship with the artist Don Bachardy, with whom he shared an openly gay lifestyle, was the subject of an award-winning documentary, Chris & Don: A Love Story; and his memoir, Christopher and His Kind, was adapted for the BBC. Isherwood's colorful journeys took him from post-World War I England to Weimar Germany to European exile to Golden Age Hollywood to Los Angeles in the full flower of gay liberation. After the publication of his diaries, which run to more than one million words and span nearly a half century, it is possible to fully assess his influence. This collection of essays considers Isherwood's diaries, his vast personal archive, and his published works and offers a multifaceted appreciation of a writer who spent more than half of his life in southern California. James J. Berg and Chris Freeman have brought together the most informative scholarship of the twenty-first century to illuminate the craft of one of the singular figures of the twentieth century. Isherwood, the American, emerges from the shadow of his English reputation to stake his claim as a significant force in late twentieth-century American culture whose legacy continues in the twenty-first century. Contributors: Joshua Adair, Murray State U; Jamie Carr, Niagara U; Robert L. Caserio, Pennsylvania State U; Niladri Chatterjee, U of Kalyani, India; Lisa Colletta, American U of Rome; Lois Cucullu, U of Minnesota; Mario Faraone; Peter Edgerly Firchow; Rebecca Gordon Stewart; William R. Handley, U of Southern California; Jaime Harker, U of Mississippi; Sara S. Hodson, Huntington Library; Carola M. Kaplan, California State U, Pomona; Benjamin Kohlmann, U of Freiburg, Germany; Victor Marsh, U of Queensland; Tina Mascara; Stephen McCauley; Paul M. McNeil, Columbia U; Guido Santi, College of the Canyons, California; Kyle Stevens, Brandeis U."--